Abivertinib, a novel BTK inhibitor: Anti-Leukemia effects and synergistic efficacy with homoharringtonine in acute myeloid leukemia. (1st October 2019) - Huang, Shujuan; Pan, Jiajia; Jin, Jing; Li, Chengying; Li, Xia; Huang, Jiansong; Huang, Xin; Yan, Xiao; Li, Fengling; Yu, Mengxia; Hu, Chao; Jin, Jingrui; et al.
Abstract: Ibrutinib, an inhibitor of Bruton tyrosine kinase (BTK), has shown promising pharmacologic effects in acute myeloid leukemia (AML). In this study, we report that abivertinib or AC0010, a novel BTK inhibitor, inhibits cell proliferation, reduces colony-forming capacity, and induces apoptosis and cell cycle arrest in AML cells, especially those harboring FLT3-ITD mutations. Abivertinib was also found to be more sensitive than ibrutinib in treating AML. We demonstrate that in addition to targeting the phosphorylation of BTK, abivertinib also targeted the crucial PI3K survival pathway. Furthermore, abivertinib suppressed the expression of p-FLT3 and the downstream target p-STAT5 in AML cells harboring FLT3-ITD mutations. Moreover, in vitro and in vivo data revealed synergistic activity between abivertinib and homoharringtonine (HHT), a natural plant alkaloid commonly used in China, in treating AML cells with or without FLT3-ITD mutations. Collectively, these preclinical data suggest that abivertinib may be a promising novel agent for AML, with potential for combination treatment with HHT. Clinical studies on abivertinib-involved therapy are planned. Highlights: Abivertinib, a novel BTK inhibitor, inhibits AML cells proliferation via BTK-dependent and independent pathway. Abivertinib and Homoharringtonine synergize to suppress AML progression in vitro and vivo. Abivertinib and Homoharringtonine synergize to down-regulated PI3K signaling.